13 Out-of-hospital cardiac arrest: evaluation of patient outcomes and impact on icu resources. (27th November 2017) - Jones, Daniel A; Koganti, Sudheer; Wragg, Andrew; Smith, Elliot J; Mathur, Anthony; Bourantas, Christos
Abstract : Background: Angiographic guidance for percutaneous coronary intervention (PCI) has substantial limitations. The superior spatial resolution of optical coherence tomography (OCT) could translate into meaningful clinical benefits, although to date limited data exists. We aimed to determine the effect on long-term survival of using OCT during percutaneous coronary intervention (PCI). Methods and Results: This was a cohort-study based on the pan-London PCI registry. In total, 1 06 880 patients are included in this registry covering London, England. All patients (n=85, 770) who underwent elective or urgent PCI in London between January 1, 2005, and May 31, 2015, were included. Patients with ST-segment elevation myocardial infarction (n = 21, 110) were excluded. The primary end point was all-cause mortality at a median of 4.1 years. OCT was used in 1042 patients (1.2%), IVUS was used in 19 356 patients (22.6%) and angiography alone in 65 372. OCT rates increased over time (p<0.0001) with variation between centres (p=0.002). A significant difference in mortality was observed between patients who underwent OCT-guided PCI (7.7%) compared with patients who underwent either IVUS (12.2%) or angiography guided PCI (15.7%, p<0.0001), with differences seen for both elective (p<0.0001) and ACS subgroups (p=0.0024). Overall this difference persisted after multivariate cox analysis (HR 0.59 (95% CI 0.20–0.90) and propensity matching (HR=0.65, 95% CI: 0.23–0.83, p=0.015) (OCT versus angio alone). Conclusion: In this large observational study, OCT-guided PCI was associated with improved long-term survival compared with standard angiography-guided PCI.